Android Media Development Based on Augmented Reality in Photosynthetic Material for PGSD UN PGRI Kediri Students - Kharisma Eka Putri; Frans Aditia Wiguna; Ahmad Hasyim Asy'ari (STAI Hubbulwathan Duri, 2022)
This study aims to produce educational media based on Augmented Reality (AR) on the photosynthesis material used in PGSD students at Nusantara PGRI Kediri University who are taking the basic concepts of Science (IPA) 2. The type of development research model used in this study is the Borg Gall model and Lee Owen with the stages of research and data collection, planning, product development, design validation, design revision. However this research is only limited to design revision after expert validation, this is due to limited research time. The instrument used in this research activity was a validity questionnaire (media expert, material expert, and linguist). Data analysis used in this research activity is descriptive qualitative data analysis and qualitative descriptive. The results of the research obtained from the media expert validator were 73 or 91%, the score of the results of the validation of the Photosynthesis material expert was 37 or 92%, and the score of the results of the validation of the linguists was 38 or 95%. This means that the development of AR-based educational media on photosynthetic material is valid, so that it can be used for learning media on photosynthetic material